PENGARUH KEPEMILIKAN INSTITUSIONAL, LEVERAGE, PROFITABILITAS, DAN KUALITAS LAPORAN KEUANGAN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA SUB SEKTOR MAKANAN DAN MINUMAN DI BEI PERIODE 2020-2024) - Tesalonika Tesalonika; Anissa Amalya Mulya (CV. Denasya Smart Publisher, 2026)
The study examines the influence of institutional ownership, leverage, profitability, and financial reporting quality on firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. A quantitative approach is employed, using a purposive sampling technique, resulting in a sample of 50 companies. The sampling criteria include: listed on the IDX until 2024; conducted their IPOs before 2020 and remained continuously listed throughout 2020-2024; published complete annual financial statements for the entire period; and had available year-end stock price data from 2020-2024. Secondary data were obtained from the official IDX website and analyzed using the SPSS program. The results show that institutional ownership and financial reporting quality do not have a significant effect on firm value. In contrast, leverage has a significant positive effect, while profitability has a significant negative effect on firm value.